Optimized Method for Isolation of Nontuberculous Mycobacteria from Hospital Aquatic Sources - Somayeh Moradi; Mohammad Javad Nasiri; Masoud Dadashi; ِDavood Darban Sarokhalil (Iranian Journal of Medical Microbiology, 2019)
Background: Aquatic ecosystems are an important source of nontuberculous mycobacteria (NTM) that can cause different diseases in human. Since culture of mycobacteria needs long-term incubation, fast-growing microorganisms and contaminants in the environment usually prevents the isolation of mycobacteria. Here, we compare different treatment protocols and describe a method that increases the recovery and improve the culturability of NTM from aqueous samples. Materials and methods: A total of 35 samples from the water sources like tap water, and medical devices such as manometer, dialysis devices, nebulizers, ventilator and dental units were collected. Containers containing 50 mL of the sample were immediately transferred for culture on Lowenstein-Jensen medium to the laboratory and examined. For better isolation of NTM, different concentrations of NaOH, sodium dodecyl sulphate (SDS), cetylpyridinium chlorid (CPC), oxalic acid and cyclohexamide in culture media were examined. Results: Culture media with 1% solution of NaOH, 3% SDS and 5% oxalic acid was completely effective to eliminate the contaminants and it also showed the lowest inhibitory effect on mycobacteria. The concentrations between 0.3 gr to 1 gr of cyclohexamide had the best inhibitory effect on growth of fungi. Conclusion: Culture media with NaOH 1%, SDS 3%, 5% of oxalic acid and 0.3-1 gr cyclohexamide can increase the recovery and improve the culturability of NTM from aqueous samples.